2017
DOI: 10.1177/0193723517747884
|View full text |Cite
|
Sign up to set email alerts
|

“Fat” Chicks Who Run: Stigma Experienced by “Overweight” Endurance Athletes

Abstract: Research on “overweight” and “obese” populations is extensive, but little of this research specifically addresses the “obese” or “overweight” amateur endurance athlete. Amateur endurance athletes often have bodies that defy the stereotype of the typical marathoner, swimmer, or triathlete. As a result, these athletes can experience stigma, both within their sporting communities as well as in the workplace, at home, and from spectators at athletic events. In an effort to discover what brings “overweight” adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
3
4
0
Order By: Relevance
“…In accordance with findings by Lewis et al [11], participants complained about gym equipment being designed only for normal-sized bodies, yet they did not mention this as a major reason for why they avoided the gym. This finding is in line with the results of a recent interview study according to which sports gear did not affect the willingness of female runners with obesity to exercise [51]. The only possible exception to this could be seen in reports about 'perceived lack of structural conformity' when participants thought that treadmills sounded too loud under their weight.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In accordance with findings by Lewis et al [11], participants complained about gym equipment being designed only for normal-sized bodies, yet they did not mention this as a major reason for why they avoided the gym. This finding is in line with the results of a recent interview study according to which sports gear did not affect the willingness of female runners with obesity to exercise [51]. The only possible exception to this could be seen in reports about 'perceived lack of structural conformity' when participants thought that treadmills sounded too loud under their weight.…”
Section: Discussionsupporting
confidence: 89%
“…The latter strategy, e.g. running at night, had also been found by Inderstrodt-Stephens and Acharya [51]. Furthermore, a recent qualitative study conducted with women by Myre and colleagues [43] reported very similar results regarding altered physical activity, such as individual activity or avoiding busy times, in response to weight stigma in PA-related contexts.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…However, negative experiences in sport and exercise settings do not necessarily have to lead to less participation. This point has already been observed by Inderstrodt-Stephens and Acharya [35] and Pearl et al [36], who suggest to differentiate between the actual stigma experience and stigma internalization. It appears not to be the discriminatory action itself (like for example an insult) but the subjective perception of this certain action as a significant personal burden that hinders PA.…”
Section: Discussionsupporting
confidence: 59%
“…In terms of socioeconomic status, about 79% of recreational runners have at least a bachelor's degree, and more than 40% make at least $75,000 per year (Running USA, 2016). The lifestyles of recreational runners reflect their predominantly middle-class status (Inderstrodt-Stephens & Acharya, 2018), as running has become increasingly embedded into leisure time. Running USA (2016) reported that 75% of recreational distance runners took an overnight trip to a race in the past 12 months.…”
Section: Recreational Running As a Site For Racial And Socioeconomic Segregationmentioning
confidence: 99%